Hesionidae Grube, 1850 (Annelida: Polychaeta) from South-Southeastern Brazil, with descriptions of four new species - Rizzo, Alexandra E.; Salazar-Vallejo, Sergio I. (Zootaxa, 2014)
On the basis of extensive intertidal and subtidal samplings in South-Southeastern Brazil, five hesionid species were found; four are newly described and Podarkeopsis levisfuscina Perkins, 1984 is redescribed. Micropodarke pleijeli n. sp. differs from the other species because it lacks eyes, and by having a large number of pharynx papillae and by neurochaetal features; this species differs from M. dubia (Hessle, 1925) by lacking eyes, having a pharynx with more papillae, and by the neurochaetal features. Syllidia amaralae n. sp. resembles more closely S. armata sensu Day, 1967 (non S. armata de Quatrefages, 1865) because both have dorsal and tentacular cirri annulated or moniliform, and 10–15 pharyngeal papillae. However, S. amaralae n. sp. specimens differ from Day’s ones because they have a quadrangular prostomium, by the relative size and arrangement of eyes, and by a reduced number of chaetae which are disposed in two bundles; these features are consistent and present in juveniles and mature specimens. Neogyptis nonatoi n. sp. is distinguishable from the others by having four types of neurochaetae; this species resembles N. crypta (Pleijel, 1993), and N. plurisetis (Hilbig, 1992). It differs from N. crypta by having a few acicular notochaetae with blunt tip, a small number of compound neurochaetae, simple capillary neurochaetae distally curved, and much slender notopodial and neuropodial lobes. The new species also differs from N. plurisetis by having four types of neurochaetae instead of having only falciger chaetae; there are less pharyngean papillae and they are far apart to each other, conical and shorter in N. plurisetis when compared to those of N. nonatoi n. sp., which are fringed, longer and closer among them, having some other longer lateral papillae. Oxydromus lanai n. sp. resembles O. obscurus (Verrill, 1873) as recorded by Uebelacker (1984), O. pugettensis by Hilbig (1994), O. guanicus by Hoagland (1919), and O. cf. guanicus by Hartman (1951). The pharynx of O. obscurus does not have fringe or papilla on its border, and it has two types of neurochaetae, differing from O. lanai n. sp. which has a single furcate notochaeta, with its shorter tine serrated. Oxydromus pugettensis and O. cf. guanicus also have usually two, instead of one, furcate notochaeta, differing from O. lanai n. sp. Oxydromus guanicus differs from our new species in having a characteristic pigmentation pattern, to be very large, its median antenna is less than one-third as long as lateral antennae, and its cirrophores are distally constricted producing a colorless ring, whereby the cirrostyle is inserted. These species are the first Brazilian records for the genera Podarkeopsis and Syllidia, and for Micropodarke, it is newly recorded from the Atlantic Ocean. Keys are included to identify hesionid genera and the species of Syllidia, Micropodarke, Neogyptis, and Podarkeopsis.